Intervensi Pengendalian Hipertensi Melalui Program Konselor di Dusun Pabuaran Desa Karyamukti Kecamtan Pataruman Kota Banjar Tahun 2025 - Vina Sabrina; Mala Nuraeni; Rini Handriani; Alika Arifiyani Ferbianti; Nazwa Salsabila; Zilfa Auliyaa Faidah; Risma Amelia Putri; Rafila Jauza Marshanda; Nawal Nur Ramadhani; Zenia Earlene Tommy Muslimin; Ninda Aulia Fitriani; Muchamad Rihan Subagja; Yuldan Faturahman (Jurnal Kabar Masyarakat, 2025)
Hypertension is a non-communicable disease whose prevalence continues to increase in Indonesia, including in Pabuaran Hamlet, Karyamukti Village, Pataruman Sub-district, Banjar City. This disease is known as the silent killer because it often does not show clear symptoms but can cause serious complications such as stroke and cardiovascular disease. Based on the results of community diagnosis in Pabuaran Hamlet, it was found that the prevalence of hypertension in this area reached 87.8% with high salt food consumption as the main risk factor. To overcome this problem, an intervention was conducted through the Konselor (Hypertension Control with Moringa Leaves) program, which aims to prevent and control hypertension by utilizing moringa leaves to reduce the effects of consuming high-salt foods. This program collaborates with Pataruman 2 Puskesmas through the Sakalor (Saimah Sakelor) program and involves various parties such as PKK cadres, especially Pokja IV, Field Agricultural Extension Workers (PPL), Women Farmers Group (KWT), and village government. The counselor's intervention activities include health education through counseling on healthy eating patterns, demonstrations on processing moringa leaves into herbal tea and procedures for planting moringa plants, as well as distribution of moringa plant seeds and leaflets to the community. The method used in developing the program uses SWOT analysis to identify internal and external factors, and the preparation of a Plan of Action (POA) as an implementation guide. The evaluation results showed that the Counselor program increased community awareness about the importance of hypertension control and how to use moringa leaves. However, several obstacles were faced, such as unoptimal community participation, uneven distribution of leaflets, and limited supporting facilities. Nevertheless, the program succeeded in initiating changes in community behavior in healthy consumption patterns. In conclusion, the Counselor Program can be an effective intervention model in community-based hypertension control. It is hoped that this program can be sustainable with the support of various stakeholders and increased community participation in implementing a healthy lifestyle, so that the incidence of hypertension in Pabuaran Hamlet can be significantly reduced in the long term.